Determination of Proper Turning Frequency to Increase for Hatching Results in Hatching Eggs With Abnormal Shape Index - Serdar Kamanlı; İsmail Türker; Hüseyin Aygören (Journal of Agricultural Sciences)
The aim of this study was to determine the optimum turning frequency for increasing the hatchability results in hatching eggs with abnormal shape index. For this purpose, 4050 hatching eggs obtained from 56 weeks old ATAK-S hybrid hens were used. Shape index was divided into 3 groups as 71 and smaller, 72 – 76, 77 and higher. The research was conducted according to a completely randomized factorial experimental design. The hatching eggs were incubated with turning frequency of 30, 60 and 120 minutes. In the present study, fertility rate, hatchability, hatch of fertile, early, middle, late embryonic mortality, discard chick rate, chick quality, malformation and malposition rates were determined. The turning frequency was found to have a significant effect on hatch of fertile eggs and late embryonic mortality. It was found that turning frequency and shape index had no significant effect on the hatching results regarding discarded chicks, early embryonic mortality, malposition, malformation rate, and chick quality. Interaction between egg shape index and turning frequency did not influence hatching traits and chick quality. It was determined that there was no interaction effect between turning frequency and shape index on all the characteristics discussed. According to the results obtained from the research, it was observed that the 30 and 120 minute turning frequency of hatching eggs with different shape indexes had a negative effect on the hatchability of fertile eggs and late embryo mortality. It was concluded that even if the shape index of the hatching eggs were different, the optimum turning frequency should be every 60 minutes.